PAI TEACHERS 'EFFORTS IN IMPROVING READING ABILITY TO WRITE THE QUR'AN THROUGH THE IQRO' METHOD IN CHILDREN WITH SPECIAL NEEDS IN SLB BINA SEJAHTERA - Nida Khofyya Hidayat; Muhammad Dahlan Rabbani; Kholil Nawawi (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
The problem of this research is to reveal the problems that occur about the efforts of Islamic Education teachers in improving the abilities of children with special needs in reading and writing the Koran through the Iqro 'method. And what are the problems of children with special needs in the ability to read and write the Koran at SLB Bina Sejahtera. This study aims to determine how Islamic Islamic education teachers are trying to improve the ability to read and write the Qur'an through the Iqro 'method, and to find out the problems of the ability to read and write the Qur'an in children with special needs in SLB Bina Sejahtera. In this study, using a qualitative method which has natural characteristics as a  source of direct data. The subject of this research is shown to the Islamic Religious Education Teacher. Researchers in this case applied several data collection techniques, namely observation, interviews and documentation. The results showed that the PAI teacher's efforts in improving the ability to read and write the Qur'an through the Iqro 'method for children with special needs, including; giving enthusiasm and affection, giving gifts, separating seats for each child, being taught one by one to do repetition of readings so that they are easy to remember and understand, as well as adding image media. The existence of this teacher's effort is able to improve the ability of children with special needs in reading and writing the Qur'an. And the problems that occur in children with special needs in reading and writing the Qur'an have different abilities.